2012
DOI: 10.1002/sia.5028
|View full text |Cite
|
Sign up to set email alerts
|

Room‐temperature diffusion coefficients for oxygen and water in UO2 matrices: a SIMS study

Abstract: To understand the mechanism of fuel oxidation, in the event of exposure of spent nuclear fuel to groundwater in a final repository, the key parameters are the diffusion coefficients for oxygen and water in UO 2 . In the temperature range relevant for geological disposal (20-100 C), we conducted static corrosion experiments, for 3-6 months, with 18 O-labelled water on different UO 2 matrices (single-crystal, polycrystalline UO 2 , SIMFUEL) so that we could evaluate the penetration of the 18 O-tracer by means of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This suggests that defects, and especially those that are concentrated within grain boundaries, may play a key role in the dissolution of UO 2 and its analogues. In spent fuel, grain boundaries are expected to contain more defects than laboratory-prepared UO 2 or UO 2 analogues, primarily due to the accumulation of fission gas bubbles and metallic precipitates; therefore, the effects of such high energy surface sites might be expected to be greater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that defects, and especially those that are concentrated within grain boundaries, may play a key role in the dissolution of UO 2 and its analogues. In spent fuel, grain boundaries are expected to contain more defects than laboratory-prepared UO 2 or UO 2 analogues, primarily due to the accumulation of fission gas bubbles and metallic precipitates; therefore, the effects of such high energy surface sites might be expected to be greater.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that defects, and especially those that are concentrated within grain boundaries, may play a key role in the dissolution of UO 2 and its analogues. In spent fuel, grain boundaries are expected to contain more defects than laboratory-prepared UO 2 or UO 2 analogues, primarily due to the accumulation of fission gas bubbles and metallic precipitates; 33 therefore, the effects of such high energy surface sites might be expected to be greater. We have observed that crystallographic orientation of the grains plays an important role in the dissolution of the grain boundaries of spent nuclear fuel analogues; grain boundaries with a high misorientation angle were found to dissolve more rapidly than those with a low misorientation angle in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…If one assumes that the Warburg element presents diffusion through the electrolyte, the diffusion coefficient (D) will be of the order of 10 À5 cm 2 s À1 , [70,71] giving rise to an L value of approximately 100 mm that is far in excess of the likely film thicknesses implied by the SEM images (Figures 1 to 3). In contrast, if the Warburg represents solid state diffusion, taking typical values of D for solid state diffusion in oxides (10 À11 to 10 À15 cm 2 s À1 ), [72,73] yields values for L from 100 nm down to 1 nm, with the upper end being consistent with the dimensions of the features as seen in the SEM images. Based on these results, we can conclude that the Warburg element arises from solid state diffusion through the oxide film rather than ionic diffusion through the electrolyte.…”
Section: Resultsmentioning
confidence: 88%